PENGEMBANGAN MULTIMEDIA INTERAKTIF LIDAMWORD BERBASIS GAMES-BASED LEARNING UNTUK MENINGKATKAN LITERASI DIGITAL PESERTA DIDIK KELAS IV SEKOLAH DASAR - Dwi Laula Amirullah; Rina Heryan; Lea Christina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the lack of understanding of class IV Elementary School X city of Bandung with the uses of basic features and supporters in the Microsoft Word and learning is still not optimal enough. This condition occurs according to researchers because there is no interactive multimedia use. Researchers aim to develop interactive multimedia LIDAMWORD to improve students’ understanding of Information and Communication Engineering (ICT) learning and make learning that attract students’ interest. The research method used is Design and Development (D&D) with the ADDIE development model (analyze, design, development, implementation, and evaluation). The research instrument used is observations, interviews, study documents, and tests. Validation outcomes of LIDAMWORD receive a value of 97.3% of the media expert, 95% of the materially, and 86% of linguist. So that these multimedias fall into the category that is very suitable for use by students. The results showed that the increase in digital literacy, with an average pre-test value of 46.6 and post-test 81.1. N-gain test shows a result of 0.63, which is currently classified, indicates that LIDAMWORD is effective in improving digital literacy, especially in Microsoft Word material.